Loitering factors and perenting relationship among adolescent secondary school students in the four states - Yahaya, Azizi (2005)
The purpose of the study is to identify the dominant factors that contribute to loitering among school students and parenting relation of adolescents. Approximately 500 students from 18 schools from Johore, Malacca, Negeri Sembilan and Selangor were selected by using cluster of cluster in this study. The data were collected using questionnaire which was adopted from Parental Behaviour Inventory (PBI), Teenagers Personality Questionnaires (TPAS) and The Parental Aspect Questionnaires (PAAS). The alpha Cronbach for this instrument for loitering factors was 0.8596, parenting styles was 0.8879 and parenting roles was 0.8975. The findings indicated that there were significant correlations with family relation factors, self-regulation teenagers, religion education, parenting styles and parents as a rolemodel. However, there were no significant differences with friendship relation and environment. Family relation factor was the most dominant factor that determine the teenagers students. The findings also shows that democratic parenting styles and parents as a role-model were in high level.